An introduction to the comparative study of private law : readings, cases, materials - Gordley, James; Jiang, Hao; Von Mehren, Arthur Taylor (Cambridge : Cambridge University Press, 2021)
This collection of readings places side by side the principal doctrines of contracts, torts, unjust enrichment, and property in the cases of the United States, England, France, Germany and China. It presents code provisions, cases, and other legal materials that describe the law in force, and places each doctrine in its historical context to enable an understanding of the development of law as an ongoing process, in which the resolution of current issues depends upon how past issues were resolved. It both provides a road map of the private law of these jurisdictions, and illustrates how private law has been shaped by history, by the effort to solve common problems, and by differences in culture. This new edition reflects changes in the law, and includes the addition of Chinese Law as a comparative study.
Title from publisher's bibliographic system (viewed on 04 Mar 2021).
Keywords: Civil law -- United States; Civil law -- England; Civil law -- France; Civil law -- Germany; Comparative law